2013
DOI: 10.1016/j.wavemoti.2013.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional numerical simulations of nonlinear acoustic streaming in standing waves

Abstract: is an open access repository that collects the work of Arts et Métiers ParisTech researchers and makes it freely available over the web where possible. AbstractNumerical simulations of compressible Navier-Stokes equations in closed twodimensional channels are performed. A plane standing wave is excited inside the channel and the associated acoustic streaming is investigated for high intensity waves, in the nonlinear streaming regime. Significant distortion of streaming cells is observed, with the centers of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 18 publications
1
20
0
Order By: Relevance
“…Fig. 1(b) shows the distorted streaming pattern (result from the numerical simulation N 2 further described in this paper) in the fast streaming regime, when two new streaming cells are observed in the center of the guide, near the acoustic velocity antinode (z/L = 0) [19,28,29]. Several sources could potentially be responsible for this mutation of streaming pattern: thermal effects were considered [26], as well as nonlinear propagation [29] and it was concluded that inertial effects on acoustic streaming could be the main source [29].…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…Fig. 1(b) shows the distorted streaming pattern (result from the numerical simulation N 2 further described in this paper) in the fast streaming regime, when two new streaming cells are observed in the center of the guide, near the acoustic velocity antinode (z/L = 0) [19,28,29]. Several sources could potentially be responsible for this mutation of streaming pattern: thermal effects were considered [26], as well as nonlinear propagation [29] and it was concluded that inertial effects on acoustic streaming could be the main source [29].…”
Section: Introductionmentioning
confidence: 89%
“…The established streaming flow behavior for high acoustic amplitudes (i.e. in the nonlinear regime of streaming) was previously analyzed numerically [19] (with a DNS code) and experimentally [28]: additional streaming cells were observed inside the resonator [29]. Fig.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The corrective terms C r i± 1 2 ,j provide the third order accuracy and upwinding for the inviscid terms. Details on the model can be found in Daru et al 14,15,22 .…”
Section: Numerical Approach a Numerical Methodsmentioning
confidence: 99%
“…For the case of thermally insulated vertical walls and differently heated horizontal walls, it was found that transverse temperature gradient strongly affects the acoustic streaming structures and velocities. 11,12 Daru et al 13 numerically studied nonlinear acoustic streaming in a closed two-dimensional gas filled channel with isothermal walls. The channel was shaken in the longitudinal direction in resonant conditions.…”
Section: Introductionmentioning
confidence: 99%